2022
DOI: 10.1002/jper.22-0091
|View full text |Cite
|
Sign up to set email alerts
|

Ion release and local effects of titanium metal particles from dental implants: An experimental study in rats

Abstract: Background The objective of this study was to evaluate the accumulation of ions in blood and organs caused by titanium (Ti) metal particles in a mandibular defect in rats, together with a description of the local reaction of oral tissues to this Ti alloy debris. Methods Twenty Sprague‐Dawley rats were randomly distributed into three groups: an experimental group with a mandibular bone defect filled with metallic debris obtained by implantoplasty; a positive control group; and a negative control group. Thirty d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Regarding Ti ions and particles, it is known that both can coexist in the peri-implant environment. A recent study showed that metal particles embedded in an experimental rat mandible defect triggered chronic inflammation with a foreign body granulomatous reaction characterized by the presence of histiocytes and MNGCs, i.e, Ti metal particles induced a chronic inflammatory cell infiltrate associated with a foreign body reaction ( 76 ). Interestingly, new evidence suggests a spatiotemporal distribution of macrophages in the FBR, therefore, a microenvironment may exist or be created within and around the biomaterial and that different macrophage phenotypes are associated with these different spaces ( 77 ).…”
Section: Stages Of Osseointegration Failurementioning
confidence: 99%
“…Regarding Ti ions and particles, it is known that both can coexist in the peri-implant environment. A recent study showed that metal particles embedded in an experimental rat mandible defect triggered chronic inflammation with a foreign body granulomatous reaction characterized by the presence of histiocytes and MNGCs, i.e, Ti metal particles induced a chronic inflammatory cell infiltrate associated with a foreign body reaction ( 76 ). Interestingly, new evidence suggests a spatiotemporal distribution of macrophages in the FBR, therefore, a microenvironment may exist or be created within and around the biomaterial and that different macrophage phenotypes are associated with these different spaces ( 77 ).…”
Section: Stages Of Osseointegration Failurementioning
confidence: 99%
“…Moreover, foreign body reaction is a complex process involving the interaction of various immune cells, and not only macrophages. [20] In another rat study, Toledano-Serrabona and colleagues [29] evaluated mandibular bone defects in Sprague-Dawley rats, filled with metallic debris obtained by implantoplasty from Ti-6Al-4V dental implants.…”
Section: In Vitro and Preclinical Studiesmentioning
confidence: 99%
“…In another rat study, Toledano-Serrabona and colleagues [ 29 ] evaluated mandibular bone defects in Sprague-Dawley rats, filled with metallic debris obtained by implantoplasty from Ti-6Al-4V dental implants.…”
Section: Effect Of Titanium Particles and Ions In Inducing Foreign Bo...mentioning
confidence: 99%
“…According to many works in the scientific literature, titanium-roughened surfaces enhance osseointegration [2] and are, therefore, available in the majority of marketed implant systems. Nevertheless, some researchers have pointed out the release of titanium ions/particles within adjacent tissues [3] as a result of tribocorrosion [4] or implantoplasty [5] and their possible role in promoting allergies, which may be underestimated due to the detection protocols being optimized for dermatology [6].…”
Section: Introductionmentioning
confidence: 99%